2010
DOI: 10.1038/ejcn.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Associations of morbidity in the underweight

Abstract: Background/Objectives: There is little research on the demographic characteristics and morbidity of people categorized as 'underweight' from their body mass index (BMI) although they have often been shown to have greater mortality. This uncertainty makes it difficult to determine whether to include or exclude these individuals when estimating the health and mortality impacts of BMI. This project compares the demographic characteristics and morbidity patterns of the underweight with those of acceptable weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
3
25
2
Order By: Relevance
“…We observed that U-shaped relationships between BMI categories and health are noted in some literature and presented in results but without emphasis [though see 27,34]. Controlling for socioeconomic, health behaviour and deprivation variables, using the Health Survey for England (2006-08), compared with persons of normal weight, we find significantly increased likelihoods of persons to report poor general health for both underweight and obese BMI categories and a slight but significant increase for persons who are overweight.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…We observed that U-shaped relationships between BMI categories and health are noted in some literature and presented in results but without emphasis [though see 27,34]. Controlling for socioeconomic, health behaviour and deprivation variables, using the Health Survey for England (2006-08), compared with persons of normal weight, we find significantly increased likelihoods of persons to report poor general health for both underweight and obese BMI categories and a slight but significant increase for persons who are overweight.…”
Section: Discussionmentioning
confidence: 67%
“…The lack of research into persons of underweight BMI in comparison with those whose BMI is higher than normal weight has been noted [27,34]. This work reveals demographic and health differences between people of different BMI categories and nonlinear associations between BMI and mental health.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations